Migration and remittances during the global financial crisis and beyond - Sirkeci, Ibrahim; Cohen, Jeffrey H. (Jeffrey Harris); Ratha, Dilip (Washington, D.C. : World Bank, 2011)
The book can be seen as a conversation between the different stakeholders involved in or affected by remittance flows globally. The book is a first-of-its-kind attempt to analyze the effects of an ongoing crisis on remittance flows globally.
Includes bibliographical references (p. 387-420) and index.
rua 01/11/13
Loan
Keywords: Emigration and immigration -- Economic aspects; Global Financial Crisis, 2008-2009.; Immigrants -- Economic aspects; Emigrant remittances -- Cross-cultural studies